Paternal Determinants in Preeclampsia - Galaviz-Hernandez, Carlos; Sosa-Macias, Martha; Teran, Enrique; Garcia-Ortiz, Jose Elias; Lazalde-Ramos, Blanca Patricia (Frontiers in Physiology, 2019)
Preeclampsia is disease with high rates of maternal-fetal morbidity and mortality. The risk to be affected varies from 3-10% in nulliparous women to 18% in previously affected women. Different lines of evidence have demonstrated the role of the father in preeclampsia development. The placenta is the cornerstone of preeclampsia and it poses important paternal genetic determinants; in fact, it has been proposed the existence of a “paternal antigen”. Nulliparity is a well-known risk factor. Preeclampsia is a condition associated with high rates of maternal-fetal morbidity and mortality. It usually occurs in 3–10% of nulliparous women and 18% of previously affected women. Different lines of evidence have demonstrated the role of the father in the onset of preeclampsia. The placenta is the cornerstone of preeclampsia and poses important paternal genetic determinants; in fact, the existence of a “paternal antigen” has been proposed. Nulliparity is a well-known risk factor. Change of partner to a woman without history of preeclampsia increases the risk; however, this change decreases in women with history of the condition. High interval between pregnancies, short sexual intercourse before pregnancy, and conception by intracytoplasmic sperm injection suggest a limited exposure to the so-called paternal antigen. A man who was born from a mother with preeclampsia also increases the risk to his partner. Not only maternal but also paternal obesity is a risk factor for preeclampsia. Fetal HLA-G variants from the father increased the immune incompatibility with the mother and are also significantly associated with preeclampsia in multigravida pregnancies. An analysis of a group of Swedish pregnant women showed that the risk for preeclampsia is attributable to paternal factors in 13% of cases, which could be related to genetic interactions with maternal genetic factors. This review aimed to evaluate the evidences of the father’s contribution to the onset of preeclampsia and determine the importance of including them in future studies.